“H” sprayer effect on liquid deposition on cucumber leaves and powdery mildew prevention in the shed - Qin, Weicai; Chen, Xuan; Chen, Panyang (Frontiers in Plant Science, 2023)
To clarify the effect of droplet size on solution deposition and powdery mildew control on greenhouse cucumber leaves, the effect of volume median droplet diameter (VMD) on solution deposition and maximum retention, as well as the effect of flusilazole on powdery mildew control on cucumber, was determined using the stem and leaf spray method. The VMD of the typical fan nozzles (F110-01, F110-015, F110-02, F110-03) of the selected US Tee jet production differs by approximately 90 μm. The results showed that the deposition of flusilazole solution on cucumber leaves decreased as the VMD of the droplets increased and that the deposition of the solution in the treatments with VMD of 120, 172, and 210 μm decreased by 22.02%, 10.37%, and 46. 97%, respectively, compared to that observed with treatment with 151 μm VMD. The deposition of the solution on cucumber leaves showed the highest deposition efficiency of 63.3% when the applied solution volume was 320 L/hm2, and the maximum stable retention of the liquid on the leaves was 6.6 µl/cm2. The control effects of different concentrations of flusilazole solution on cucumber powdery mildew differed significantly, and the best control effect was achieved at the dosage of 90 g/hm2 of the active ingredient, which was 15%−25% higher than that observed at the dosage of 50 and 70 g/hm2 of the active ingredient per hectare. A significant difference in the effect of droplet size on the control of cucumber powdery mildew was observed at any specific liquid concentration. Nozzle F110-01 showed the best control effect when the dosage of the active ingredient was 50 and 70 g/hm2 per hectare, which did not differ significantly from that observed with nozzle F110-015 but differed significantly from those observed with nozzles F110-02 and F110-03. Hence, we concluded that the use of smaller droplets with VMD of 100−150 μm, i.e. the choice of F110-01 or F110-015 nozzles, for application on the leaf parts of cucumber in the greenhouse under conditions of high liquid concentration, can significantly improve the effective use of pharmaceuticals and the disease control effect.